SYSTEM DYNAMICS APPROACH FOR WHOLE LIFE CYCLE COST MODELLING OF RESIDENTIAL BUILDING PROJECTS IN UNITED ARAB EMIRATES - Sadek, Ahmed (2020)
Purpose – Project management field is experiencing many challenges to maintain its performance and delivery within planned time, budget, and quality. Latest research focused on cost modelling and estimation. There is a high demand to have many developments within a short period and acceptable quality. The significance of cost modelling comes from the forecasted information value. This research study aims to model project's whole life cycle costs of residential buildings in UAE at the preconstruction stage, choosing VENSIM system dynamics approach. The objective is to simulate dynamically cost over time for all outputs. Design/methodology/approach – The approach of this research is pure quantitative. It requires mapping diagrams and mathematical computation systems. Research questions were answered as a gear unit to build the final cost model. Identifying cost risks values are the first required answer. These values are extracted from field experts. Data validity and reliability are conducted using mechanistic (hypotheses) mathematical models (correlation and regression). Adjusting cost risks are computed using Monte Carlo stochastic mathematical model. Finally, VENSIM system dynamics final cost model is developed approaching empirical, dynamic (stock and flow), and deterministic mathematics. Findings – The result of system dynamics approach investigation revealed that it can model project's total expenditure (TOTEX) dynamically over time, including cash flow and NPV. Limitations – The model’s verification process could not verify OPEX estimation accuracy due to the absence of OPEX real data in UAE. This is because UAE age (≈ 50 year) is less than the model's lifecycle (60 years). The model is developed for residential buildings in UAE. This requires further investigation to check the ability of system dynamics approach to model costs for other project types and/or in other geographical regions. It is required to check the model's response against changing/adjusting the used mathematical system to ensure the maximum accuracy of system dynamics approach for cost modelling. It is compulsory to investigate system dynamics cost modelling response against adapting deferent demolition scenarios. Theoretical implications – The final system dynamics cost model is incorporating TOTEX cash flow and net present value estimates for each time step across the project's whole life cycle at the preconstruction stage. This is achieved by applying adjusting risks on project's initial cost at the preconstruction stage with respect to cost and risk behaviours at each time step. Cost impact is following an increasing S-Curve behaviour during CAPEX time and risk impact is following a decreasing S-Curve behaviour during CAPEX lifetime. Both cost and risk impacts are linearly increasing during OPEX lifetime. And NPV is following a negative exponent behaviour over TOTEX lifetime. The applied adjusting risks are comprising three value levels. Minimum, mean, and maximum cost risks. Simulated costs under adjusting risks' levels can be presented in the same exported data sheet. All cash flow scenarios, under three cost risks levels, can be trended in the same chart, simultaneously, including all project's lifecycle time steps. Practical implications – TOTEX and NPV accurate estimation outputs are the most important criteria for future investments decisions. In addition, modelling project's cash flow is the most helpful approach to apply stochastic area method (easy-to-apply) analysis. Multiple scenarios provide better understanding of future events. Originality/value – This research significant contribution to the project management body of knowledge is accomplished by providing the first cost model, approaching system dynamics, for residential building projects' whole lifecycle.